Pelatihan Digital Marketing Bagi Kelompok Pemberdayaan Kesejahteraan Keluarga (PKK) di Desa Sukorejo Kabupaten Gresik sebagai Upaya Penguatan Branding dan Pemasaran Produk Lokal - Zakiyyati, Qurrota Ayun; Abdul Hakam; Ajrina Valentine Marhadyta; Risma Ayu Kinanti; Ubaidillah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STAI Al Fithrah Surabaya, 2025)
This community service activity aims to improve the digital literacy and marketing skills of the women of the Sukorejo Village PKK through digital marketing training as an effort to strengthen branding and expand the market reach of local products. The activity was held on Sunday, August 24, 2025, at the Sukorejo Village Hall with 25 participants. The implementation method consisted of three stages, namely preparation, face-to-face training, and online mentoring. The training material covered an understanding of the basic concepts of digital marketing, the practice of creating promotional content using Canva, and effective branding strategies to attract consumers in the digital era. The training results showed a significant increase in the participants' knowledge and skills in utilizing digital platforms for product promotion. Participants were able to produce creative graphic designs and felt more confident in managing marketing independently through social media. Overall, this activity contributed to women's empowerment through enhanced digital capacity and strengthened technology-based economy, while also supporting the development of knowledge in the fields of community education and creative economy. Keywords: Digital Marketing, PKK, Branding, Local Products